Respuesta :
Y = 6 * 4x. x = -3
Y = 6 ((4 * (-3))
Y = 6 * (-12)
Y = -72
This should be right if I understood the question correctly.
Y = 6 ((4 * (-3))
Y = 6 * (-12)
Y = -72
This should be right if I understood the question correctly.
ANSWER
[tex]y = - 72[/tex]
EXPLANATION
The given function rule is
[tex]y = 6 \times 4x[/tex]
We want to evaluate this function for
[tex]x = - 3[/tex]
We just have to substitute -3 into the function rule to obtain,
[tex]y = 6 \times 4( - 3)[/tex]
This is the same as,
[tex]y = 6 \times - 12[/tex]
This will evaluate to,
[tex]y = - 72[/tex]
[tex]y = - 72[/tex]
EXPLANATION
The given function rule is
[tex]y = 6 \times 4x[/tex]
We want to evaluate this function for
[tex]x = - 3[/tex]
We just have to substitute -3 into the function rule to obtain,
[tex]y = 6 \times 4( - 3)[/tex]
This is the same as,
[tex]y = 6 \times - 12[/tex]
This will evaluate to,
[tex]y = - 72[/tex]